16- DETECTION OF BRUCELLA SPECIES IN APPARENTLY HEALTHY COWS AND GOATS RAW MILK BY PCR - Fawzia A. Abdullah; Enas Ismael Al- Jaboury (Basrah Journal of Veterinary Research)
Brucellosis an intracellular pathogen capable of infecting animals and humans. The aim of this study was to identify Brucella spp in apparently healthy cow and goat raw milk samples by a polymerase chain reaction (PCR)-based method. A total of 75 cow milk samples(55 direct and 20 indirect) and 50 goat milk samples were examined by PCR. To establish a PCR protocol for diagnosis of brucellosis, DNA was extracted from the milk samples by using a commercial kit. PCR amplification was done for detection of Brucella DNA using BCSP31 target gene and IS711 locus. The PCR assay showed that an amplicon of 223 bp was obtained in 28% (21/75) and 8% (4/50) samples of cow and goat tested milk using primers (B4/B5) derived from aBCSP31gene encoding the 31-kDa Brucella abortus antigen. In another PCR, an amplicon of 498 bp was obtained in 100% (21/21) of the brucella genus BCSP31-PCR positive cow milk samples using Brucella abortus-specific primers derived from a locus adjacent to the 3’-end of IS711, and also an amplicon of 731 bp was produced in 100% (8/8) of the BCSP31-PCR positive goat milk samples using Brucella melitensis-specific primers.PCR positive results for brucella genus and brucella abortus species were observed in all (100%) cow,s milk samples(n=11) with clinical history of abortion.As a single PCR product, no B. abortus was detected in goat milk samples alsoB. Melitensis was not detected in cow milk samples